2013
DOI: 10.1176/appi.ajp.2012.12030386
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Older Age and More Successful Aging: Critical Role of Resilience and Depression

Abstract: Background There is growing public health interest in understanding and promoting successful aging. While there has been some exciting empirical work on objective measures of physical health, relatively little published research combines physical, cognitive, and psychological assessments in large, randomly selected, community-based samples to assess self-rated successful aging (SRSA). Methods In this Successful AGing Evaluation (SAGE) study, we used a structured multi-cohort design to assess successful aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
346
3
21

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 418 publications
(394 citation statements)
references
References 49 publications
24
346
3
21
Order By: Relevance
“…Mental health factors such as resilience, other positive traits (e.g. wisdom, optimism), and absence of depressive symptoms are also predictors of successful aging [7][8][9][10]. Consistent with the known physical and behavioral components of successful aging, healthy lifestyle (e.g.…”
Section: Predictors Of Successful Agingmentioning
confidence: 85%
See 1 more Smart Citation
“…Mental health factors such as resilience, other positive traits (e.g. wisdom, optimism), and absence of depressive symptoms are also predictors of successful aging [7][8][9][10]. Consistent with the known physical and behavioral components of successful aging, healthy lifestyle (e.g.…”
Section: Predictors Of Successful Agingmentioning
confidence: 85%
“…functioned in the community without disability, in excellent or good health, and with high cognitive functioning; [16]. In San Diego-based community samples of older adults, we have found that a sizable proportion of older adults rate themselves as aging successfully independent of the presence of diseases and disabilities [9].…”
Section: Predictors Of Successful Agingmentioning
confidence: 95%
“…En un estudio realizado se analizaron las diferencias entre las personas resilientes y no resilientes ante la situación de duelo, concluyó como la mayoría de las personas resilientes, también experimentan dolores de anhelo y emocionales, cognición intrusiva y rumia, en algún momento poco después de la pérdida, pero, en las personas resilientes, estas experiencias son transitorias (Bonanno, 2004), además la resiliencia se asocia, también, con la aceptación de la muerta y la creencia en un mundo justo (Bonanno et al, 2002). En líneas generales, en los estudios se ha concluido que existe una relación positiva entre la resiliencia y la recuperación de la sintomatología depresiva, es decir, que los pacientes con mayor nivel de resiliencia presentan menor nivel de depresión (Boardman et al, 2011;Catalano, Chan, Wilson, Chiu, & Muller, 2011;Jeste et al, 2013;Seok et al, 2012). , realizaron un estudio con pacientes con depresión y/o trastornos de ansiedad, en el que identificaron como la baja espiritualidad era un predictor importante de los grupos de menor resiliencia; el bajo propósito en la vida, el escaso el ejercicio físico y el rasgo de ansiedad severa se asociaron con los grupos de baja y media resiliencia.…”
Section: Resiliencia Y Salud Mentalunclassified
“…Following those suggestions, studies have incorporated indicators of mental health, such as depressive symptomatology, in operational definitions of successful ageing (Kok et al 2017). Even if depression is not considered to be part of successful ageing, it is strongly associated with it (Jeste et al 2013).From the perspective of public health, it has been clear that the burden of depressive problems has been a considerable challenge to healthy population ageing (Murray & Lopez, 1997). Given the multitude of risk factors for depression in modern society and given the consequences of depressive problems, investigating resilience in relation to depression seems an obvious route toward identifying entry points for reducing the burden of morbidity.…”
mentioning
confidence: 99%
“…Following those suggestions, studies have incorporated indicators of mental health, such as depressive symptomatology, in operational definitions of successful ageing (Kok et al 2017). Even if depression is not considered to be part of successful ageing, it is strongly associated with it (Jeste et al 2013).…”
mentioning
confidence: 99%